Two Challenges to the Theory of Rights: Immigration and Cultural Pluralism - Asis, Rafael de (2009)
This paper approaches the conception of human rights from the recognition of two constants: equality and difference. The author argues that it is necessary to consider both constants when analyzing and developing the projection of rights. Along these lines, immigration and cultural pluralism are used as frameworks for understanding contemporary human rights challenges. Finally, the author reflects on the impact of globalization on the conception of human rights and the management of cultural diversity. The author closes the analysis by proposing the conception of a dynamic theory of rights that understands the relevance of cultural diversity in their construction.